Media convergence as a growth factor connected with cases of language norm violations in mass media - Ekaterina Andreyevna Baranova; Evgeniya Leonidovna Karich (RUDN Journal of Studies in Literature and Journalism, 2018)
In 2009-2017 years E.A. Baranova talked with journalists, editors and top managers of Russian media companies on topics related to the development of media convergence in the newsrooms of Russia mass media. During these years, 86 respondents from 30 media companies were interviewed. Analysis of empirical data and conceptual comprehension of a wide range of works, as well as personal experience in the media allowed the author to conclude that the media convergence process associated with the constant increase in information flows; development of user generated content and the blogosphere; journalism transformation as a types system of professional activity; economic difficulties faced by many media companies leads toreduction of literacy rate for journalists, an incensement number of spelling and stylistic errors in the mass media. The article also presents an analysis of errors in the texts of print and broadcast media. The purpose of the article is to present the problem situation and actualize the need for the subsequent comprehension of the problem of the fall of language media culture in the aspect of axiology.